Determinants of community participation in community policing program in Malaysia - Sulaiman, Abdul Hadi; Othman, Jamilah; Abu Samah, Bahaman; Yero, Aliyu; Alby, Jeffrey Lawrence D'Silva; Rodriguez, Adriana Maria Ortega (Asian Network for Scientific Information, 2014)
Understanding the factors that influence community participation in neighbourhood is vital in developing a successful community policing program in Malaysia. The aim of this study is to highlight the factors that influence participation of community using the socio-ecological model. Five factors were identified and they are individual, community, organizational and governmental factors. The findings helped in developing a conceptual model that could serve as an useful resource for future study.